Study on the Risk Prevention Measures of China’s Network Payment from the Perspective of Regulators - Chu Yu; Yingchun Deng (Law and Economy, 2022)
Since the beginning of the 21st century, China’s Internet has developed rapidly, and the rapid development of the network has driven the creation and rapid spread of online transactions across the country. It is in this context that a new kind of intermediate trading platform has been developed, which has rapidly swept through the lives of the public in the past decade. From the perspective of finance, supplemented by personal research, the author begins the article by clarifying the meaning of China’s network payment and other related concepts and briefly introduces the development of network payment at home and abroad in recent years, analyzing and listing the risks and their causes in the development of network payment; then introduces the relevant documents and measures taken by China for the regulation of network payment and analyzes the current Then, we introduce the relevant documents and measures taken by China’s online payment regulation and analyze the dilemma faced by China in preventing the risk of online payment under the current regulatory policy, and further conclude the risk prevention countermeasures to improve the regulation of online payment in China.